The Effectiveness of Flashcards Media in Increasing Parents' Knowledge and Perceptions about The Reproductive Health of Elementary School-Age Children - Kusumaningrum, Tanjung Anitasari Indah; Kusumawati , Yuli; Inayati , Nurul Latifatul; Umaroh, Ayu Khoirotul; Hidayat, Muhamad Taufik; Livia, Wardhatul; Syifa, Asy; Trijaya; Nabilla, Nur Jihan Luthfia; Nugroho, Purwo Setiyo (Public Health of Indonesia, 2025)
Background: Elementary school-age children need to get reproductive health information, but parents still have negative perceptions and a lack of knowledge about reproductive health in elementary school children. Objectives: This study aims to analyze the effectiveness of using flash cards as educational media to improve parents' knowledge and perceptions of reproductive health education in elementary school-age children. Methods: This quasi-experimental study was conducted with a pretest-posttest control group design in June 2024. The participants in this research were parents of children in grades 1-3 at two elementary schools in Kartasura, with 32 people in the experimental group and 32 in the control group. Statistical analysis used a paired t-test for knowledge, and a Wilcoxon signed rank test for perception. The effectiveness of flashcards on parents' knowledge was tested with an independent t-test, and perception was tested with the Mann-Whitney U test.  The significance level was 5%. Results: The result was an increase in the mean score of knowledge (p-value<0.001) and perception (p-value=0.023) in the intervention group. The mean score did not increase in the control group on these variables. The intervention and control groups differed in parents’ average knowledge (p-value=0.0496) and perception (p-value=0.0036) regarding reproductive health. Conclusions: Flashcards effectively improved parents' knowledge and perceptions about reproductive health education.